PENGARUH KONSELING KESEHATAN PRA NIKAH TERHADAP PENUNDAAN KEHAMILAN BERESIKO OLEH PASANGAN USIA REMAJA DI UPT PUSKESMAS KLAKA - SUTIYOWATI SUTIYOWATI; IIT ERMAWATI; YESSY NUR ENDAH SARY (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Education or counseling has a significant influence on teenage couples because it affects the perspective of receiving health information. Communication, Information and Education health material in the form of reproductive health knowledge and gender equality. The purpose of this study was to analyze the effect of premarital health counseling on risky pregnancy delays in prospective teenage couples at the Klakah Health Center. The research design used was correlation research. The population of this study were teenage couples who visited the Klakah Health Center in 2022 using a total sampling technique. The independent variable in this study was premarital health counseling and the dependent variable in this study was the delay in risky pregnancies by teenage couples. The instrument in this study used medical records and the mother's Cohort. Data analysis used the Chi square test with a significant level of 0.05. From the results of the study, it was found that most of the teenage couples delayed pregnancy, namely 45 people (76.3%) and 14 couples who did not delay pregnancy (23.7%). The results of the Chi square test showed that p = 0.00 <0.05, so H0 was rejected or H1 was accepted, there was an effect of premarital health counseling on delaying risky pregnancies by teenage couples at the Klakah Health Center. As health workers, it is hoped that they can provide premarital health counseling, especially for teenage couples so that they can delay their pregnancies.